2013
DOI: 10.1002/kpm.1414
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering the Knowledge Audit Process: Methodological Revisions in Practice

Abstract: Over the last 20 years, the knowledge audit and map have been acknowledged as important tools in helping to identify and visually represent the knowledge present in organizational contexts. Despite this recognition and the availability of theoretical material, there has been a dearth of literature relating to the application of these tools. Consequently, a number of methodologies based on KM practice and research emerged in the early 2000s; several of which still inform the knowledge audit and map processes to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Although the previous steps are quite similar to those proposed by some previous authors of KA methods, there still remains few guidelines on how to link the analysis to a KM strategy that an organization can adopt to align its knowledge resources' to the business requirements (Burnett et al, 2013). In order for the previous analysis to fruitful for KM improvements, this step can detect problems and propose solutions.…”
Section: 4mentioning
confidence: 89%
See 2 more Smart Citations
“…Although the previous steps are quite similar to those proposed by some previous authors of KA methods, there still remains few guidelines on how to link the analysis to a KM strategy that an organization can adopt to align its knowledge resources' to the business requirements (Burnett et al, 2013). In order for the previous analysis to fruitful for KM improvements, this step can detect problems and propose solutions.…”
Section: 4mentioning
confidence: 89%
“…We found that it was useful, even necessary, to add on an additional step to classify the di®erent solutions into various KM projects. As previously noted, the experts involved in the analysis are better placed to produce a more e®ective and successful KM strategy (Burnett et al, 2013). This strategy can then be presented to top management for approval and¯nancing.…”
Section: 5mentioning
confidence: 98%
See 1 more Smart Citation
“…Cheung et al (2007) carried out KA of a railway company which eight phases were used; the researchers recommended to the management the creation of organizational culture where employees could share idea, experience and expertise; establish incentive programs to motivate them to add to KM activities, top management support for adoption of KM. Levantakis et al (2008) proposed a reference method of KA, which was applied to engineering department; which identified four procedures in KA which are defining the outline of the new reference method; activities divided into sub-activities, compare the reference method with existing audit methods, they compared it with Orna (1999), Henczel (2013), Burnett et al (2013), Perez-Soltero et al, (2006) methods to see similarities and differences; selection of method fragments and assembly of the new reference method and the final stage was validation of the KA methods. Also Roberts (2008) carried a KA of a Dutch ICT company, where 58 consultants working on clientele site were located in Netherland which was carried out for two months with the use of questionnaire and interviews.…”
Section: Definition Of Knowledge Auditmentioning
confidence: 99%